Boron and chlorine abundances in Antarctic chondrites: A PGA study - Oura, Yasuji; Takahashi, Chieko; Ebihara, Mitsuru (National Institute of Polar Research, 2004)
P(論文) Boron and chlorine abundances were determined by prompt gamma-ray analysis for Antarctic meteorites of 22 carbonaceous chondrites and 12 ordinary chondrites. Both B and Cl contents of most Antarctic meteorites analyzed in this study are systematically higher than those for non-Antarctic chondrites of corresponding groups, implying that Antarctic meteorites of carbonaceous and ordinary chondrite groups were contaminated with not only Cl (and other halogens like I) but also B. Boron and Cl contents are correlated with each other in Antarctic ordinary chondrites whereas no apparent correlation can be seen for carbonaceous chondrites. Considering that interior portions were used for carbonaceous chondrites while interior and outer portions were randomly sampled for ordinary chondrite used in this study, B and Cl are distributed differently between the two groups of chondrite, suggesting that B and Cl independently behaved following their own chemical properties after contaminant(s) carrying these elements adhered on the surface of meteorites. Sea mist is a probable candidate for such a contaminant. Leaching experiments showed that no B is essentially recovered by water and acetone even from pulverized specimens, from which a fairly large fraction of Cl is recovered, confirming that B and Cl reside independently in chondrite samples and further that both elements behaved differently after sticking to these samples on Antarctica. departmental bulletin paper